The Effect of Second Home Tourism on Improving the Economic Situation of the Rural Residents in Central District of Taleqan County - Tamimi, Leili; Jafari, Hamid; Alizadeh, Katayoon; Qanbarzadeh Darban, Hadi (International Journal of Psychosocial Rehabilitation, 2021)
oday, second home tourism is an important factor for the development of rural areas. Hence, the effects of second home tourism on improving the life quality of rural residents in the central district of Taleqan county have been studied in the present research. The research method of this study is applied in terms of purpose and descriptive-analytical in terms of method. The field and library methods have been used to collect data. The research tools were a questionnaire related to the research hypothesis that was distributed among the families of the sample villages and the results were analyzed. The inclusion criteria for sample villages were those that had the capacity to be called tourism second homes from the perspective of tourism experts and researchers; therefore, seven villages (30% of the population) were selected as the sample of the study. The content validity of the questionnaire was confirmed through Delphi technique and the reliability of different parts was obtained using Cochran's alpha. After data collection and processing, the findings of the research indicated that second home tourism has been able to provide positive effects on the improvement of rural residents’ economic status.